The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.7150/thno.70896
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory endothelium-targeted and cathepsin responsive nanoparticles are effective against atherosclerosis

Abstract: Rationale: Atherosclerosis is characterized by lipid accumulation, plaque formation, and artery stenosis. The pharmacological treatment is a promising therapy for atherosclerosis, but this approach faces major challenges such as targeted drug delivery, controlled release, and non-specific clearance. Methods: Based on the finding that the cathepsin k (CTSK) enzyme is enriched in atherosclerotic lesions, we constructed an integrin α v β 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Atherosclerosis, a CVD, is mainly caused by endothelial injury accompanied by many inflammatory reactions. These reactions result in the oxidation of low-density lipoprotein (LDL) by macrophages to form peroxide and superoxide ions, SMC proliferation, and plaque formation in the vascular wall [ 81 ]. TQ was found to be involved in this process and is mainly effective in reducing the level of LDL to prevent foam cell formation through an antioxidant function.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis, a CVD, is mainly caused by endothelial injury accompanied by many inflammatory reactions. These reactions result in the oxidation of low-density lipoprotein (LDL) by macrophages to form peroxide and superoxide ions, SMC proliferation, and plaque formation in the vascular wall [ 81 ]. TQ was found to be involved in this process and is mainly effective in reducing the level of LDL to prevent foam cell formation through an antioxidant function.…”
Section: Discussionmentioning
confidence: 99%
“…This emerging field of research in drug delivery holds significant promise. In a study conducted by Fang et al, 88 NPs were engineered to target integrin αvβ3 and respond to the enzyme cathepsin K (CTSK) for controlled release of the drug RAP. It was discovered that CTSK is enriched in atherosclerotic lesions.…”
Section: Nanoparticles For Controlled Release Of Drugs In Application...mentioning
confidence: 99%
“…Currently, the most-studied polymeric NPs for anti-atherosclerosis are hyaluronic acid (HA)-based and PLGA-based NPs. 95–99 Recent studies have shown that HA NPs can actively target atherosclerotic plaques. 100 Hossaini Nasr et al assessed the anti-atherosclerosis effect of HA NPs loaded with the clinical drug atorvastatin and found that, compared to in the free atorvastatin group, the group with HA-NPs loaded with atorvastatin experienced a better anti-inflammatory effect in vivo and in vitro after 1 week of treatment.…”
Section: Organic Nps For Atherosclerosis Treatmentmentioning
confidence: 99%